Cost modelling system for lean product and process development - Ahmad, Wasim (Cranfield University, 2012)
This PhD project aims to develop a cost modelling system to support lean product and process development. The system enables the designers to assess the design along with associated manufacturing processes and provides decision support at an early development stage. Design assessment at early development stage can help designers to take proactive decisions, eliminate mistakes and enhance product value. The developed cost modelling system to support lean product and process development incorporates three lean product and process development enablers, namely set-based concurrent engineering, knowledge-based engineering, and mistake-proofing (poka-yoke). To facilitate above explained lean enablers, the system architecture contains six modules, six separate groups of database, a CAD modelling system, and a user interface. The system modules are: (i) value identification; (ii) manufacturing process/machines selection; (iii) material selection; (iv) geometric features specification; (v) geometric features and manufacturability assessment; and (vi) manufacturing time and cost estimation. The group of database includes: (i) geometric features database, (ii) material database, (iii) machine database, (iv) geometric features assessment database, (v) manufacturability assessment database, and (vi) previous projects cost database. A number of activities have been accomplished to develop the cost modelling system. Firstly, an extensive literature review related to cost estimation, and lean product and process development was performed. Secondly, a field study in European industry and a case study analysis were carried out to identify current industrial practices and challenges. Thirdly, a cost modelling system to support lean product and process development was developed. Finally, validation of the system was carried out using real life industrial case studies. The system provides a number of benefits, as it enables designers to incorporate lean thinking in cost estimation. It takes into consideration downstream manufacturable process information at an early upstream stage of the design and as a result the designer performs the process concurrently and makes decisions quickly. Moreover, the system helps to avoid mistakes during product features design, material and manufacturing process selection, and process parameters generation; hence it guides toward a mistake-proof product development. The main feature of the system, in addition to manufacturing cost estimation, is set-based concurrent engineering support; because the system provides a number of design values for alternative design concepts to identify the feasible design region. The major contribution of the developed system is the identification and incorporation of three major lean product and process development enablers, namely set-based concurrent engineering, knowledge-based engineering and poka-yoke (mistake-proofing) in the cost modelling system. A quantification method has been proposed to eliminate the weaker solution among several alternatives; therefore only the feasible or strong solution is selected. In addition, a new cost estimation process to support lean product and process development has been developed which assists above explained three lean product and process development enablers.
Keywords: Lean product development; Cost Modelling; Set-based concurrent engineering; Knowledge-based engineering; Mistake-proofing (poka-yoke)